Answers

2015-09-21T14:36:30+05:30
-5a²b+3ab²+11-7a²b+8ab²-18
=-12a²b+11ab²-7
0
hi ! you should also give the calculation....
i mean the process in which the answer is solved
2015-09-21T14:45:13+05:30
-5a²b + 3ab² + 11 - 7a²b + 8ab² - 18
Arrange the variables in order and then find the answer.
= -5a²b - 7a²b + 3ab² + 8ab² + 11 - 18
= -12a²b + 11ab² - 7
0
its not -5a^2b -7a^b=-12a^2b
its not 12a^b
its -12a^b
ohhhh i got it sorry actually i forgot about that - sign thanks for telling!
dnt mention it